Myth-making, community, and catholic tradition - Mcgarry, Francis J. (Journal of religion and health, 1991)
Assuming that myths and their stories are among the most prominent vehicles for teaching spiritual values and creating communities of faith, the purpose of this paper is to examine myth relative to its nature, role, and function. The presence of myth in society also allows for the evaluation of those myths that are evil. In addition to that, we have the inappropriateness of certain aspects of myths that need to be identified and removed, lest they contaminate the whole story and its spiritual effect.Each of these issues is addressed, and certain suggestions are made relative to greater community wholeness and spiritual well-being.